Marsialap Ari sebagai Tradisi Gotong Royong dan Dinamika Solidaritas Sosial dalam Masyarakat Agraris Angkola-Mandailing - Muhajir, Ahmad (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This article aims to investigate the culture of gotong royong originating from the Angkola-Mandailing ethnicity, especially related to their thick agrarian life. The focus is on a tradition of mutual aid called marsialap ari. This research also uses qualitative methods by analyzing literature sources and conducting field research. Data sources used include observation, interviews, and documentation. Emile Durkheim's theory of social solidarity sees the relevant practice of mutual aid in the marsialap ari tradition of the Angkola-Mandailing community. This practice reflects the values of togetherness, solidarity, and shared trust that are the basis of social solidarity. The results of the study can be concluded that the marsialap ari tradition in the Angkola-Mandailing community is a clear example of strong mutual assistance, where residents help each other in agricultural work voluntarily. This tradition builds a sense of community, cooperation, and joy in carrying out agricultural duties. Although threatened by individualistic values, modern agricultural technology, and shifting values of society, marsialap ari remains important as a mirror of social values that build character, mutual trust, and togetherness in society.